2012
DOI: 10.1111/jam.12009
|View full text |Cite
|
Sign up to set email alerts
|

Arthrobotrys oligospora -mediated biological control of diseases of tomato (Lycopersicon esculentum Mill.) caused by Meloidogyne incognita and Rhizoctonia solani

Abstract: Aims: To study the biocontrol potential of nematode-trapping fungus Arthrobotrys oligospora in protecting tomato (Lycopersicon esculentum Mill.) against Meloidogyne incognita and Rhizoctonia solani under greenhouse and field conditions. Methods and Results: Five isolates of the nematode-trapping fungus Arthrobotrys oligospora isolated from different parts of India were tested against Meloidogyne incognita and Rhizoctonia solani in tomato (Lycopersicon esculentum Mill.) plants grown under greenhouse and field c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 40 publications
1
29
0
Order By: Relevance
“…More importantly, two identified species (Arthrobotrys oligospora, Acremonium sclerotigenum) may play an important role in the micro-ecological of R. glutinosa rhizosphere according to previous reports. It was confirmed that A. oligospora not only increased the plant growth and enhanced nutritional value of tomato but also functioned in controlling nematodes (Niu and Zhang 2011;Singh et al 2013;Yang et al 2011a). A. sclerotigenum was confirmed to be the pathogen of brown spot disease in apple .…”
Section: Discussionmentioning
confidence: 87%
“…More importantly, two identified species (Arthrobotrys oligospora, Acremonium sclerotigenum) may play an important role in the micro-ecological of R. glutinosa rhizosphere according to previous reports. It was confirmed that A. oligospora not only increased the plant growth and enhanced nutritional value of tomato but also functioned in controlling nematodes (Niu and Zhang 2011;Singh et al 2013;Yang et al 2011a). A. sclerotigenum was confirmed to be the pathogen of brown spot disease in apple .…”
Section: Discussionmentioning
confidence: 87%
“…Bands at 25,575 cm −1 could be attributed to charge transfer band. [38] Nickel(II) complex has a magnetic moment of 3.15B. M. indicating high-spin octahedral configuration.…”
Section: Solid Reflectance and Magnetic Studiesmentioning
confidence: 99%
“…It is used to control plant-parasitic nematodes, especially Meloidogyne spp. (Singh et al, 2012(Singh et al, , 2013. A. oligospora conidial germination is repressed by soil fungistasis (Liu, 2019), making it a suitable model organism for researching the mechanisms behind soil fungistasis relief by nutrients.…”
Section: Introductionmentioning
confidence: 99%